Less is more! Rapid increase in plant species richness after reduced mowing in urban grasslands - Sehrt, Melissa; Bossdorf, Oliver; Freitag, Martin; Bucharova, Anna (Basic and applied ecology, 2020)
Urban lawns provide space for recreation in cities, and they are an important part of urban green infrastructures. However, most lawns are intensively managed. As only few plant species can survive frequent mowing, urban lawns typically harbor only a limited number of plant species. To improve the biodiversity of urban lawns, it is often suggested to reduce the mowing frequency. Here, we studied the plant diversity of urban grasslands that have recently undergone management changes from mowing every few weeks to mowing only once or twice per season and compared them to intensively managed lawns. Within six years after the management changes, the grasslands with reduced mowing frequency hosted 30% more plant species than intensively managed lawns, and they were more heterogeneous both within and between grasslands. Additionally, the species composition of less frequently mown grasslands shifted from common mowing-tolerant lawn species to typical meadow species. Our study thus shows that the reduction of mowing is a simple and effective tool for increasing the biodiversity in urban grasslands.